Pembinaan Akhlak Siswa melalui Program Shalat Dhuha Berjamaah di MIN 1 Siak - Muawanah; Moh. Irmawan Jauhari (PT. Saha Kreasi Indonesia, 2025)
This study aims to analyze the role of the congregational Dhuha prayer program in developing students’ character at MIN 1 Siak. The program is implemented as an effort to strengthen character education by instilling religious values through routine and structured religious activities. The research employed a qualitative method with a case study approach, in which data were collected through observation, interviews, and documentation. The findings indicate that the consistent implementation of the congregational Dhuha prayer is able to enhance students’ spiritual awareness, foster discipline, develop a sense of responsibility, and improve positive social interactions among students. These outcomes significantly contribute to the formation of good moral character in accordance with Islamic values. Thus, the congregational Dhuha prayer program serves as an effective model for student character development within the madrasah environment.